Diagnosis and Treatment of Pseudo-Class III Malocclusion - Reyes, Ariel (Case Rep Dent, 2014)
Pseudo-Class III malocclusion is characterized by the presence of an anterior crossbite due to a forward functional displacement of the mandible; in most cases, the maxillary incisors present some degree of retroclination, and the mandibular incisors are proclined. Various types of appliances have been described in the literature for the early treatment of pseudo-Class III malocclusion. The objectives of this paper are to demonstrate the importance of making the differential diagnosis between a skeletal and a pseudo-Class III malocclusion and to describe the correction of an anterior crossbite. The association of maxillary expansion and a 2 × 4 appliance can successfully be used to correct anterior crossbites.